Nursing diagnoses of patients with kidney disease undergoing hemodialysis: a cross-sectional study - Dandara Novakowski Spigolon; Elen Ferraz Teston; Fábio de Oliveira Souza; Bruna dos Santos; Rebeca Rosa de Souza; Antônio Moreira Neto
ABSTRACT Objective: to identify Nursing Diagnoses of 5th stage chronic kidney disease patients undergoing hemodialysis. Method: cross-sectional, descriptive and quantitative study carried out with 151 patients undergoing hemodialysis in a clinic specialized in nephrology from the Northwest of the Paraná State. Nursing Diagnoses were determined through Nanda-I in which had the percentage greater than 50%. The analysis used was the simple statistics. Results: 17 Nursing Diagnoses were identified, emphasizing the risks present in 100% of patients: risks for electrolyte imbalance; ineffective kidney perfusion; infection: vascular injuries, adverse response to the iodine-based contrast-enhanced and impaired urinary elimination. Conclusion: the main diagnoses listed reflect the more frequent risks that patients undergoing hemodialysis are exposed to. Being aware of these risks allows the nursing planning with early interventions, in order to prevent complications related to the disease and to promote best life conditions.